2021
DOI: 10.4108/eai.7-7-2021.170284
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Boykov's graph cuts based segmentation for Cervical Cancer Detection

Abstract: Introduction: Cervical cancer is considered as the major curse to women society of the world due to their low survival rate. However, the prognosis of cervical cancer at an early stage through periodic screening was identified to enhance the survival probability of the women patients around the world. Objective: In this paper, a Boykov-Kolmogorov Graph Cuts and Cloud Model-based Synergy Integrated Segmentation (BKGC-CMSIS) Technique for facilitating predominant cervical cancer detection from the pap smear imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Mustafa et al, [27] reported the sensitivity achieved is about 94.38%, while Lavanya Devi and Thirumurugan [4] achieved 97.96%. The specificity of the nuclei segmentation technique is 82.56% and 83.65% and has been demonstrated in these two reports [25].…”
Section: Review Of the Study 21 Nucleus Segmentationsupporting
confidence: 54%
See 3 more Smart Citations
“…Mustafa et al, [27] reported the sensitivity achieved is about 94.38%, while Lavanya Devi and Thirumurugan [4] achieved 97.96%. The specificity of the nuclei segmentation technique is 82.56% and 83.65% and has been demonstrated in these two reports [25].…”
Section: Review Of the Study 21 Nucleus Segmentationsupporting
confidence: 54%
“…Furthermore, an edge augmentation approach relying on mathematical morphology and the canny operator is provided, which retrieves edge information as a weight to boost the nucleus edge specifically [24]. The Boykov-Kolmogorov Graph Cuts (BKGC) scheme is suggested from a study by Balaji et al, [25]. It presents an efficient BKGC-based image partitioning approach that predicts the image data utilizing a synergy cloud model to form objective functions.…”
Section: Review Of the Study 21 Nucleus Segmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cervical cancer is a major disease that seriously threatens women’s health [ 1 , 2 ]. This cancer is also known as the second most commonly affected and killer type of cancer among women around the world [ 3 ].…”
Section: Introductionmentioning
confidence: 99%